Development of Patent License in the Post Issuance of Law No. 11/2020 on Job Creation - Rizki Pratiwi (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
Patent license has a great effects on a country’s advancement since it included technological creation which can increase its economic condition. In a patent lisence contract, Article 7 of the TRIP’s Agreement states that HKI protection and enforcement should be provide the contribution to technological transfer deployment by paying attention to balanced interest. Besides that, one of their benefits is for the nation’s advancement. However, Law No. 11/2020 on Job Creation has eliminated the obligation to transfer technology in giving the patent license in Indonesia. The research problems are as follows: how about the legal comparison of the obligation of technological transfer in the patent license according to TRIP’s Agreement, Law No. 13/2016 on Patent, and Law No. 11/2020 on Job Creation with the implementation of Patent License agreement in Indonesia, and how about the development of the patent license from the issuance of Law No. 13/2016 on patent until the issuance of Law No. 11/2020 on Job Creation. The research employs juridical normative method with descriptive analytical approach. Secondary date are collected by conducting library research. They are analyzed qualitatively by using deductive method. The result of the research shows that amendment of Article 20 of law on Job Creation in giving the patent has eliminated the regulation on the obligation to transfer technology in giving the patent which has the implication on the human resource development in Indonesia. The technological transfer has given great advantages of the advancement of economic development, the increase in domestic and foreign investments, the advancement of social development.